Patterns of Antibiotic Indication and Selection in Early-onset Neonatal Infections at a Provincial Obstetrics and Pediatrics Hospital - Trang, Tran Thi Thu; Hang, Le Thi Thu; Thao, Nguyen Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4DO - 10.25073/2588-1132/vnumps.4775, 2025)
Abstract: Objective: Subject and method: A cross-sectional study was conducted among patients with medical records of systemic antibiotic use at the Neonatal Department of a provincial Obstetrics and Pediatrics Hospital from November 2022 to December 2022. Results: The study enrolled 137 patients, who were mainly full-term infants (78.8%) and had adequate birth weight (81.0%). Most cases of suspected neonatal infections were general, with no clear localization (99.3%). The proportion of patients undergoing microbiological testing was low (5.1%). Most patients were given appropriate empirical antibiotics (89.1%). The most frequently prescribed initial regimens were monotherapy with ampicillin-sulbactam (54.0%) and a combination of ampicillin/sulbactam and gentamicin (41.6%). The proportion of appropriate initial empiric regimens to the guidelines was 43.8%. In this study, 29 patients changed their antibiotic regimen, which mainly involved antimicrobial de-escalation. Conclusion: Most patients in this study were eligible for empirical antibiotics. However, the proportion of patients choosing monotherapy regimens was high, with 43.8% consistent with the guidelines. Microbiological testing should be considered to discontinue antibiotic use. Keywords: Early-onset neonatal infections, early-onset neonatal sepsis, antibiotics.